Improving Content Quality through Standardized Photos, Vertical Videos, and Captions for BAZNAS Cilacap MSMEs - Annisa Romadloni (Universitas Kristen Cipta Wacana, 2025)
The principal challenges faced by the micro, small, and medium enterprises supported by the National Amil Zakat Agency of Cilacap Regency are inconsistent visual-content quality, the absence of a simple workflow, and weak security and copyright-compliance practices, which together lead to unstable performance across digital channels. The community service set out to design and evaluate an intensive, practice-based training that standardizes the production of product photographs, short vertical videos, and promotional captions, while also instilling account governance and publishing routines. The method used a two-day field-action design with target outputs per participant of one set of photographs, one video, and three promotional captions; output quality was assessed with a five-point rubric. The findings indicate that the output reached the “publishable” category, with mean scores near the midpoint of the scale. It is concluded that a simple, standardized training model can stabilize content quality and encourage early improvements in digital-channel performance; extending the monitoring period and improving link tagging are recommended to demonstrate more convincingly the connection between platform activity and transactions.